Peran Edukatif dan Sosial Guru PAI dalam Mewujudkan Sekolah Ramah Tanpa Bullying di MAN 1 Pidie - Nada Afra; Nanda Saputra (Yayasan Madinah Al-Aziziyah, 2026)
Bullying in the school environment remains a serious issue that affects the psychological and social development of students. This study aims to analyze the educational and social roles of Islamic Religious Education (PAI) teachers in preventing and addressing bullying behavior at MAN 1 Pidie. The study employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving PAI teachers, the madrasah principal, and students. The findings indicate that PAI teachers play a strategic role in creating a friendly and religious school climate through learning activities that instill moral values, empathy, and Islamic brotherhood (ukhuwah Islamiyah). In addition, the teachers’ social role is reflected through role modeling, character development, and personal interaction with students who experience or engage in bullying. The consistent efforts of PAI teachers contribute to the formation of a harmonious madrasah environment that respects differences and is free from verbal and physical violence.